A Document on the Economic Status of the Lutsk Karaites in the Mid-19th century - Sulimowicz, Anna (Karaite Archives, 2014)
Among the various documents preserved in the community’s archives is a handwritten list containing the names, properties and professions of the Lutsk Karaites. Compiled in 1854, it provides data about various economic and social aspects of the community’s life in the mid-19th century. It is also a valuable source of information on anthroponomy and genealogy. In the article, the content of the manuscript is presented, as well as additional information obtained through a comparison with other sources.